2015
DOI: 10.24925/turjaf.v3i6.406-412.380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Slaughter Weights on Slaughter and Carcass Traits of Male Karayaka Lambs Reared under Intensive Production System

Abstract: The present study was conducted to investigate the carcass traits of Karayaka lambs slaughtered at different slaughter weights (SWs) and to find out optimum SWs. Male Karayaka lambs with 20 kg live weight (n=30) constituted the animal material of the study. Lambs were randomly divided into five SW groups; 30 (GI; n=6), 35 (GII; n=6), 40 (GIII; n=6); 45 (GIV; n=6) and 50 (GV; n=6) kg. Lamb fattening feed (concentrate feed, ad libitum) and forage (lentil straw, 100g/lamb/day) were used as the feed material. Lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
7
4
0
Order By: Relevance
“…Hot carcass dressing percentage determined in the semiintensive group was lower than the value (49.09%) reported by Macit et al [29] , for Tuj lambs under semiintensive conditions, similar to the values under semiintensive conditions (46.78%) stated by Kırmızıbayrak et al [23] for Tuj lambs and (47.56% and 47.64%) stated by Sarı et al [22] . The highest cold carcass dressing percentage was in intensive group and it is in agreement with the results in intensive group observed by Carrasco et al [26] , Aksoy and Ulutaş [30] , Akçapınar et al [31] , and Joy et al [32] . Cold carcass dressing percentages (41.58-48.42%) of Tuj male lambs of the present study were similar to values of the different fatting systems reported by Aksoy and Ulutaş [30] (45.34-48.44%), Akçapınar et al [31] (47.15%) and Koçak et al [33] (44.17-45.57%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Hot carcass dressing percentage determined in the semiintensive group was lower than the value (49.09%) reported by Macit et al [29] , for Tuj lambs under semiintensive conditions, similar to the values under semiintensive conditions (46.78%) stated by Kırmızıbayrak et al [23] for Tuj lambs and (47.56% and 47.64%) stated by Sarı et al [22] . The highest cold carcass dressing percentage was in intensive group and it is in agreement with the results in intensive group observed by Carrasco et al [26] , Aksoy and Ulutaş [30] , Akçapınar et al [31] , and Joy et al [32] . Cold carcass dressing percentages (41.58-48.42%) of Tuj male lambs of the present study were similar to values of the different fatting systems reported by Aksoy and Ulutaş [30] (45.34-48.44%), Akçapınar et al [31] (47.15%) and Koçak et al [33] (44.17-45.57%).…”
Section: Discussionsupporting
confidence: 81%
“…The highest cold carcass dressing percentage was in intensive group and it is in agreement with the results in intensive group observed by Carrasco et al [26] , Aksoy and Ulutaş [30] , Akçapınar et al [31] , and Joy et al [32] . Cold carcass dressing percentages (41.58-48.42%) of Tuj male lambs of the present study were similar to values of the different fatting systems reported by Aksoy and Ulutaş [30] (45.34-48.44%), Akçapınar et al [31] (47.15%) and Koçak et al [33] (44.17-45.57%).…”
Section: Discussionsupporting
confidence: 81%
“…In order to improve the production efficiency and to develop products that are suited to customer demands it is important to understand the growth and development and the factors affected (Rashid et al, 1987). The latest study has shown no significant differences in the percentage of carcass dressings of different slaughter weights, however, with increased slaughter of male Karayaka lambs, increasing fat levels and decreasing percentage of carcass lean and bone have been observed (Aksoy and Ulutaş, 2015). The main aim of this study was to demonstrate that Karadi male lambs were slaughtered with different weight for optimal slaughtering weight, carcass characteristics and meat sensory evaluation.…”
Section: Introductionmentioning
confidence: 87%
“…In order to increase yields in sheep production, genotype and environmental conditions should be improved. Hence, it has been reported that in the intensive finishing conditions of 2-3 months in Turkey, a carcass weighing 18-20 kg can be produced from a postweaned lamb of 2-3 months old (3)(4)(5)(6)(7). Based on these data, we can conclude that intensive production systems are necessary to satisfy increasing consumer demand for meat.…”
Section: Introductionmentioning
confidence: 95%
“…Concordantly, numerous studies have been conducted to determine the slaughter and carcass characteristics used in developed countries (8)(9)(10). Recently, various studies have also been performed to determine the slaughter and carcass characteristics of indigenous breeds in Turkey (6,7,(11)(12)(13)(14)(15)(16). However, there has been very little information about the carcass characteristics and body measurements of Herik lambs under finishing systems (17); the current study has taken steps to investigate the slaughter and carcass characteristics of Herik lambs under intensive finishing conditions.…”
Section: Introductionmentioning
confidence: 99%